2006
DOI: 10.2134/jeq2005.0351
|View full text |Cite
|
Sign up to set email alerts
|

Ground Cover Impacts on Sediment and Phosphorus Export from Manured Riparian Pasture

Abstract: Maintaining pasture ground cover is important in preventing environmental degradation of grasslands and associated riparian areas. The objective of this work was to determine the effect of ground cover on sediment and P export from pastured riparian areas under simulated rainfall events. Plots were established on two sites in the North Carolina Piedmont: a 10% slope with Appling sandy loam soils (fine, kaolinitic, thermic Typic Kanhapludults) and a 20% slope with Wedowee sandy loam soils (fine, kaolinitic, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…However, average sediment runoff concentrations were greater during the non-winter period than the winter period, showing that rainfall-induced runoff was more erosive than snowmelt runoff. Overall though, data clearly show that well-established pasture vegetation can effectively eliminate soil erosion (Owens et al, 1983b;Butler et al, 2006;Bartley et al, 2010).…”
mentioning
confidence: 97%
“…However, average sediment runoff concentrations were greater during the non-winter period than the winter period, showing that rainfall-induced runoff was more erosive than snowmelt runoff. Overall though, data clearly show that well-established pasture vegetation can effectively eliminate soil erosion (Owens et al, 1983b;Butler et al, 2006;Bartley et al, 2010).…”
mentioning
confidence: 97%
“…Not surprisingly, concentration of sediment in surface runoff has been linearly related to the amount of bare ground of a given area, as exposed soil is more susceptible to soil detachment by overland flow (Hofman and Ries 1991;Elliott et al 2002;Persyn et al 2004) and erosive energy of raindrops (Young and Wiersma 1973;Morgan 1978;Kinnell 2005). As a result, bare ground in riparian areas of pastures may contribute significant sediment and phosphorus loads to surface waters during heavy rainfall events (Line et al 2000;Byers et al 2005;Butler et al 2006). Although stocking rate did not affect the proportion of bare ground within 15.2 m of pasture streams in the current study, measuring bare ground from each stream's edge likely confounded the effects of cow traffic on the proportion of bare ground with those caused by precipitation runoff and erosive energy of the stream flow (Tufekcioglu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Western rangelands have shown that maintaining adequate vegetation contributes to prevention of degradation of riparian areas (Butler et al 2006;Schoonover et al 2006) and NPS of pasture streams by providing cover and resistance to erosion (Klemmedson 1956;Kauffman and Krueger 1984;Trimble 1994). Vegetation cover provides resistance to topsoil detachment by reducing raindrop forces (Hofman and Ries 1991;Pearce et al 1998) and may limit concentrated flow and runoff events (Self-Davis et al 2003;De Baets et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of cattle grazing and horse riding emphasize the importance of large animal traffic on soil erosion, but few studies were cited that actually measured erosion rates from trails during storm events (Trimble and Mendel, 1995; Pickering et al, 2010). Most of the relevant research that has actually measured sediment production has focused on plot‐scale (e.g., Warren et al, 1986; Butler et al, 2006) or catchment‐scale (e.g., Johnson and Smith, 1978; McDowell, 2007) results that may include effects of animal trails along with a wide array of other disturbances on sediment production. Many other studies have used proxies to link grazing and animal use pressures to sediment production (e.g., Anderson, 1974; Trimble and Mendel, 1995; Foster et al, 2007).…”
mentioning
confidence: 99%